Making Use of Relicts: Brisingid Seastars Aggregate on Hydrothermally Inactive Sulfide Chimneys Near Black Smokers - Woods, Daniel; Cheadle, Michael J.; John, Barbara E.; German, Christopher R.; Van Dover, Cindy L. (Frontiers in Marine Science, 2022)
When hydrothermal activity ceases at black-smoker chimneys on mid-ocean ridges, populations of associated invertebrates hosting chemoautotrophic endosymbionts decline and then disappear, but the chimneys can persist on the seabed as relicts. Suspension-feeding brisingid seastars colonize hydrothermally inactive (relict) chimneys on the East Pacific Rise (EPR), though their distribution relative to available hard substrata and proximity to hydrothermal activity is poorly documented. In this study, brisingid abundance on sulfide and basalt substrata was assessed along an ∼3,700 m ROV Jason II transect at the summit of Pito Seamount (SE Pacific; ∼2,275 m). Brisingids were non-randomly distributed, with highest densities (up to ∼300 m–2) on relict sulfides chimneys near active black smokers. Brisingids were relatively uncommon on basalt substrata, and absent on black smokers. We infer that both relict sulfide structures and proximity to black smokers play key roles in the maintenance of dense brisingid populations on Pito Seamount and in similar environments on the EPR. Our observations suggest that experimental introduction of “artificial” relict chimneys providing microtopographic relief could test whether such an approach might mitigate potential impacts of mineral extraction on populations of suspension-feeding invertebrates.